Variations and Phenetic Analysis of Peanut Cultivars (Arachis hypogaea L.) Based on Morphological Characteristics - Purnomo Purnomo; Nurul Khotimah (Universitas Gadjah Mada, 2019)
Peanut (Arachis hypogaea L.) is a food commodity that is widely cultivated in Indonesia. At present there has been no analysis of the relationship between peanut cultivars with phenetic methods based on the morphological properties of the plants. Four cultivars of Arachis hypogaea L. Tuban, Talam 1, Talam 2, and Talam 3 used in this research. Morphological characters data was analyzed by description to construct identification key. Similarity index was counted by Simple Matching Coefficient (SSm) formula based on morphological scoring. Cluster analysis was conducted by UPGMA (Unweighted Pair Group Methods using Arithmetic Averages) method to construct dendrogram. PCA (Principal Component Analysis) were performed to defined role of each morphological character in grouping of accessions with MVSP (Multivariate Statistical Program) v. 3.1 software. The dendrogram showed that four cultivars of Arachis hypogaea L. divided into two main clusters, 4 sub-clusters. The similarity index of clusters is 0.85%.